Manajemen Risiko Pada Kantor Perwakilan PT. Arminareka Perdana Pariaman Dalam Menghadapi Pandemi Covid-19 - Azhia Nova; Khadijah Nurani (Universitas Pahlawan Tuanku Tambusai, 2023)
This research is a field research conducted at PT. Arminareka Perdana Pariaman Representative Office. This research uses descriptive qualitative research. Source of data obtained from primary and secondary data. Where the primary data obtained from the leadership of PT. Arminareka Perdana Pariaman Representative Office while secondary data were obtained from books, journals. Data analysis uses the Miles and Huberman models with the stages of data reduction, data modeling, verification/drawing conclusions. The results of field research show that during the Covid-19 pandemic PT. Arminareka Perdana Pariaman Representative Office continues to operate to reduce the anxiety and worries of prospective pilgrims and the public, and always try and try their best to broadcast even in the conditions of the Covid-19 pandemic. Keywords : Risk Management, Covid19, Pandemic